Factors Affecting Tourism Demand in Maldives - Chok, Yee Cher (Universiti Malaysia Sarawak, (UNIMAS), 2019)
The role of tourism in the economy is very significant, providing many job opportunities and an important part of the development cycle taking place in any country's economy. This paper analyzes the determinants for tourism in Maldives from the top ten countries. A collection of data from the panel is gathered from 2010 to 2018. The balanced panel model is used to analyze the relationship between nominal gross domestic product, exchange rate and transport costs of the top ten countries with the number of tourists arriving in Maldives. The results showed that the nominal gross domestic product, exchange rate and transportation costs of the top ten countries co-integrate with the number of tourist arrivals. Additionally, the variables have a unidirectional and bidirectional relationship. The results of the model are therefore important because it can give policymakers and related authorities an insight into attracting more international tourists.